Integrated signaling and transcriptome analysis reveals Src family kinase individualities and novel pathways controlled by their constitutive activity - Koutras, Nikolaos; Morfos, Vasileios; Konnaris, Kyriakos; Kouvela, Adamantia; Shaukat, Athanasios-Nasir; Stathopoulos, Constantinos; Stamatopoulou, Vassiliki; Nika, Konstantina (Frontiers in Immunology, 2023)
The Src family kinases (SFKs) Lck and Lyn are crucial for lymphocyte development and function. Albeit tissue-restricted expression patterns, the two kinases share common functions, the most pronounced one, being the phosphorylation of ITAM motifs in the cytoplasmic tails of antigenic receptors. Lck is predominantly expressed in T-lymphocytes; however, it can be ectopically found in B-1 cell subsets and numerous pathologies including acute and chronic B-cell leukemias. The exact impact of Lck on the B-cell signaling apparatus remains enigmatic and is followed by the long-lasting question of mechanisms granting selectivity amongst SFK members. In this work we sought to investigate the mechanistic basis of ectopic Lck function in B-cells and compare it to events elicited by the predominant B-cell SFK, Lyn. Our results reveal substrate promiscuity displayed by the two SFKs, which however, is buffered by their differential susceptibility towards regulatory mechanisms, revealing a so far unappreciated aspect of SFK member-specific fine-tuning. Furthermore, we show that Lck- and Lyn-generated signals suffice to induce transcriptome alterations, reminiscent of B-cell activation, in the absence of receptor/co-receptor engagement. Finally, our analyses revealed a yet unrecognized role of SFKs in tipping the balance of cellular stress responses, by promoting the onset of ER-phagy, an as yet completely uncharacterized process in B-lymphocytes.